LANGERHAN CELL HISTIOCYTOSIS: A CHILD PRESENTING WITH NINE MONTHS HISTORY OF FEVER - Khan, Jauhar Mumtaz; Dar, Nasser Rashid; Tahir, Moizza; Janjua, Wasif Ali (Journal of Ayub Medical College Abbottabad, 2014)
We report a case of Langerhan Cell Histiocytosis in a three and a half years old child. The child presented with history of low grade fever, off and on for 9 months. There was 2 months history of progressive pallor and 5 days history of epistaxis. Blood complete picture revealed pancytopenia and the patient was referred to a paediatric oncologist. Initial diagnosis of acute lymphoblastic leukaemia (ALL), Lymphoma and disseminated Tuberculosis (TB) was made on basis of initial investigations. Coetaneous involvement occurred 7 months later along with Diabetes Insipidis, bone changes and pulmonary involvement. Keywords: Fever, Langerhan cell histiocytosis, lymphoma, cutaneous